The Circuit Games Modification to Stimulate the Manipulative Movement for Kindergarten student - Ardini, Pupung Puspa (Indonesian Journal of Early Childhood Education Studies, 2019)
This research aims to determine (1) the difference in manipulative movement ability between children given circuit and ball games. (2) Differences in the ability of manipulative movements of children given circuits and ball games with high social interaction, (3) Differences in the ability of manipulative movements of children given circuits and ball games with low social interaction, (4) Interactions between games and social interaction with manipulative movement ability. This research was conducted in Gorontalo City. A total sample are 48 children in grade B (age between 5-6 years) and using the Simple Random Sampling technique. The method in this research is the experiment and the design is factorial 2x2 treatment by level. Analysis of the research is ANAVA (Analysis Varians) which was then followed by the Tuckey test. The results of the study: (1) There are differences in the ability of manipulative motion between children given circuit and ball play (2) There are differences in the ability of manipulative movements of children given circuits and ball games with high social interaction, (3) There are differences in the manipulative ability of children who are given circuit games and ball games with low social interaction, (4) There is an interaction between the game and social interaction with manipulative ability. Keywords : Games, circuit,Ball, Social Interaction, Manipulative Movement